Elegance and National Expression in Artistic Translation (Poetic and Prose) - Musayeva Guzal Ne’matillayevna; Ummataliyev Firdavs To’lqinali o’g’li (Peerian Journals Publishing, 2023)
This article highlights and discusses the peculiarities of literary translation, the rules of law, the re-creation of national expressions in prose and prose translations and some shortcomings and successes through examples
Keywords: artistic translation; national characteristic; poetic translation; national expression